"Given to You by Nature for an Enemy": The Landlady in Mid-century London. (18th April 2018) - Boggs, Molly
Abstract: The domestic novel and the family home are closely associated with mid-century Victorian culture, but less attention has been paid to narratives about lodging-house life. These prose essays and short stories, published in huge numbers from the 1840s through the 1860s in London magazines, reached an audience of middle-class readers eager to read about home spaces defined not by comfort and security, but by invasions of privacy, frustration, and awkward social encounters. The most important figure in representations of lodging-houses was the landlady, portrayed as the cruel, calculating despot of the lodging's domestic sphere: the antithesis of the ideal mid-century wife. The landlady was represented by the striving authors behind these semi-autobiographical narratives as a formidable enemy, challenging what they saw as their right to deferential service from a wife or mother figure. These expectations jarred with the landlady's own economic needs in the widespread business of urban accommodation. This essay examines a number of mid-century lodging-house narratives, paying particular attention to Charles Dickens's popular story about a landlady, 'Mrs Lirriper's Lodgings' (1863).